Anti-obesity Effect of Gymnema sylvestre Extract on High Fat Diet-induced Obesity in Wistar Rats - Kumar, V.; Bhandari, U.; Tripathi, C. D.; Khanna, G. (Drug Research, 2013)
Gymnema sylvestre R. BR. (Asclepiadaceae) has been used frequently in traditional Indian folk medicine for the treatment of diabetes. Study was performed in high fat diet (HFD)-induced obesity in murine model. Obesity was induced by oral feeding of HFD for 28 days. The anti obesity effect of water soluble fraction of Gymnema sylvestre extract (120 mg/kg, p.o. for 21 days) in HFD fed rats was evaluated by the measurement of body weight gain, food intake, hemodynamic changes (systolic, diastolic, mean blood pressure and heart rate), serum lipid profiles (triglycerides, total cholesterol, LDL-cholesterol, HDL-cholesterol), leptin, insulin, glucose, apolipoproteins A1 and B, lactate dehydrogenase (LDH) and antioxidant enzymes such as reduced glutathione (GSH), glutathione peroxidase (GPx), glutathione reductase (GR), glutathione-S transferase (GST), superoxide dismutase (SOD) and catalase (CAT) levels in liver tissues. Organs and visceral fat pad weight were measured. Histopathological studies were also carried out. Water soluble fraction of G. sylvestre ethanolic extract and rimonabant significantly reduced serum lipids, leptin, insulin, glucose, apolipoprotein B and LDH levels while it significantly increased the HDL-cholesterol, apolipoprotein A1 and antioxidant enzymes levels in liver tissue as compared to the HFD fed rats. Histopathological studies of tissues showed no pathological changes. The results of this study show that water soluble fraction of G. sylvestre extract possess antiobesity effect.
Keywords: Gymnema sylvestre; leptin; insulin; apolipoproteins; antioxidant enzymes